Evaluation of semiconducting p-type tin sulfide thin films for photodetector applications. (September 2019) - Barman, Biswajit; Bangera, Kasturi V.; Shivakumar, G.K.
Abstract: Tin sulfide (SnS) is an important semiconductor as it is one of the less common p-type materials with a bandgap of 1.53 eV which makes it an attractive material for photo detector application. In the thin film form, it is a sensitive photo conductor with attractive opto-electronic characteristics. In the current report, tin sulfide thin films have been deposited by thermal evaporation in vacuum and the influence of substrate temperature on its compositional, morphological, structural, and opto-electrical properties was studied. X-ray diffraction (XRD) study shows that all the thermally deposited films are having an orthorhombic crystal structure along (111) plane as pre-dominant orientation and are polycrystalline in nature. Raman analysis verify the occurrence of SnS and Sn2 S3 phases in the films. Surface morphology along with the elemental composition of the films was determined by scanning electron microscopy (SEM) in combination with energy dispersive spectroscopy (EDS). All the films were found to be homogeneous, uniform, pin-hole free and have high optical transmittance in the UV–Vis wavelength region. The optical bandgap energy of the films was calculated using Tauc's relation and it was found to be decreasing (1.576 eV–1.429 eV) with increasing substrate temperature. The activation energy of the SnS thin films was calculated from Arrhenius plot and it was also found to be decreasing with increasing substrate temperature. The opto-electrical parameters such as photo conductivity (σL ), dark conductivity (σD ), response time (τr ), recovery time (τd ), photoresponsivity (R), and photosensitivity (S) were calculated and was found best for the films grown at 323 K. Highlights: SnS thin films of thickness ∼500 nm were grown at various substrate temperatures by thermal evaporation technique. The effect of substrate temperature on visible light photodetector behavior of glass/SnS/Ag is reported for the first time. Raman along with XRD analysis shows the presence of SnS and Sn2 S3 phases on the deposited films. Stochiometric SnS films were achieved at a substrate temperature of 323 K. Films grown at 323 K displayed better photosensitivity along with least photo response and recovery time.